Cost-effectiveness of direct oral anticoagulants in non-valvular atrial fibrillation - Inigo Gorostiza; Amaia Bilbao-Gonzalez; Javier Mar (Gaceta Sanitaria)
Objective: There is evidence on the efficiency of new direct oral anticoagulants (DOAC), mostly based on experimental efficacy data, but there is also a need to assess their cost-effectiveness in routine clinical practice using patient-level data. We designed a retrospective cohort study to assess the cost-effectiveness of DOAC compared to acenocoumarol in patients with non-valvular atrial fibrillation (NVAF) with a follow-up of up to 7 years. Method: Basque Health Service-registered patients who started oral anticoagulant treatment between 2013 and 2016 were included in the study and followed up until the end of 2019. Data were extracted from an electronic medical record management system. Effectiveness was expressed in terms of life years gained and adjusted for health-related quality of life (i.e., quality-adjusted life years [QALY]). Propensity score techniques were used to adjust the estimates for differences between groups in baseline characteristics. Results: A total of 10,843 new users of oral anticoagulants with a mean follow-up of 4.1 years were included. The incremental cost-effectiveness ratio of DOAC compared to acenocoumarol ranged from €1,732 to €2,556/QALY, while the incremental net benefit for different willingness-to-pay thresholds was only negative for values below €3,000/QALY. Conclusions: Based on the analysis of data from clinical practice and the similarity of results using several different techniques to adjust for bias associated with observational studies, we conclude that DOAC would be an efficient alternative for the treatment of patients with NVAF. Resumen: Objetivo: Existe evidencia de la eficacia de los nuevos anticoagulantes orales directos (ACOD), basadas sobre todo en datos experimentales, pero también es necesario evaluar su coste-efectividad en la práctica clínica habitual utilizando datos del paciente. Se diseñó un estudio de cohortes retrospectivas con el objetivo de evaluar el coste-efectividad de los ACOD en comparación con acenocumarol en pacientes con fibrilación auricular no valvular (FANV), con hasta 7 años de seguimiento. Método: Se incluyeron pacientes del Sistema Vasco de Salud (Osakidetza) que comenzaron un tratamiento anticoagulante entre 2013 y 2016, siendo seguidos hasta finales de 2019. Los datos se extrajeron de las historias clínicas electrónicas. La efectividad se expresa como años de vida ganados y años de vida ajustados por calidad (AVAC). Se emplearon distintas técnicas de ajuste propensity score para limitar el impacto de las covariables sobre los resultados. Resultados: Se incluyeron 10.843 nuevos usuarios de fármacos anticoagulantes, con un seguimiento medio de 4,1 años. La ratio coste-efectividad incremental de los ACOD comparados con acenocumarol varió entre 1.732 € y 2.556 € por AVAC, mientras que el beneficio neto incremental para distintas disponibilidades a pagar solo resultó negativa para valores inferiores a 3.000 € por AVAC. Conclusiones: Teniendo en cuenta que se parte de datos provenientes de la práctica clínica habitual y la obtención de resultados consistentes empleando distintas técnicas de ajuste propias de los estudios observacionales, se concluye que los ACOD pueden ser una alternativa eficiente en el tratamiento de los pacientes con FANV.